The Impact of Developments in the Logistics Sector on Economic Growth: The Case of OECD Countries - Hayaloğlu, Pınar (International Journal of Economics and Financial Issues, 2015)
Logistic sector, which is considered as an important interface of increased international trade in consequence of globalization, plays an important role on countries’ economic growth and development. A development in logistic sector facilitates the international trade, increases the competitiveness in countries and thus appears to be an important determinant of growth and development. In this study, the impact of developments in the logistic sector on economic growth has been investigated for 32 OECD countries covering the period 1994-2011. In this context, static panel data analysis was used. The findings obtained in the study, which used different variables as indicators of developments in the logistic sector, reveals that the relationship between developments in the logistic sector and economic growth differs depending on the indicator used. Keywords: Logistic Sector, Economic Growth, Telecommunications, OECD Countries JEL Classifications: L80; L86; O40